Preparation of nanocrystalline MgNb2O6 by citrate gel method - Pasricha, R; Ravi, V (Materials Letters, 2005)
A gel was formed when a aqueous solution of Mg(NO3)(2), NbF5 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 700 degrees C produced the fine crystallites of ternary oxide, MgNb2O6 (MN). The formation of MN phase and lattice parameters were determined by the powder X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Citrate gel; Electron microscopy; magnesium niobate; powders; X-ray diffraction

Synthesis of Ce0.75Zr0.25O2 at 100 degrees C - Dhage, S. R.; Gaikwad, S. R.; Muthukumar, P.; Ravi, V. (Ceramics International, 2005)
A simple gel to crystal conversion route has been used for the preparation of Ce0.75Zr0.25O2 phase at 80-100degreesC under refluxing conditions. Freshly prepared metal hydroxides gel from cerium and zirconium salt solution is allowed to crystallize under refluxing and stirring conditions for 4-10 h. Formation of nano crystallites of Ce0.75Zr0.25O2 is confirmed by X-ray diffraction (XRD). Transmission electron microscopy (TEM) investigations revealed the average particle size of these powders to be 5 nm. (C) 2004 Elsevier Ltd and Techna S.r.l. All rights reserved.
Keywords: CeO2; chemical preparation; Electron microscopy; powders; X-ray methods

Synthesis of nanocrystalline rutile - Samuel, V; Pasricha, R; Ravi, V (Ceramics International, 2005)
Nanocrystalline titanium dioxide (TiO2) in the rutile phase has been obtained by homogeneous precipitation using urea and TiOCl2. A mixture of urea and TiOCl2 is heated on a hot water bath at 65-75 degrees C to precipitate rutile powders. X-ray diffraction (XRD) studies on these oven-dried powders indicated the formation of single-phase rutile. Raman scattering experiments were also performed to confirm the formation of the rutile phase. Transmission electron microscopy (TEM) investigations revealed the average particle size of these powders to be 40 nm. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: chemical preparation; Electron microscopy; powders; TiO2; X-ray methods

Novel hydroxide precursors to prepare NaNbO3 and KNbO3 - Muthurajan, H.; Kumar, H. H.; Samuel, V.; Gupta, U. N.; Ravi, V. (Ceramics International, 2008)
Firstly, fresh niobium, hydroxide was precipitated from NbF5 solution using an aqueous ammonium hydroxide under basic conditions. Then a simple procedure of mixing potassium (or sodium) and niobium hydroxides together and heating at a low temperature (<400 degrees C) produced KNbO3 (KN) or NaNbO3 (NN) powders. This is the lowest temperature so far reported for the formation of these phases. The phase content and lattice parameters are determined by X-ray diffraction (XRD). The average particle size and morphology were studied by scanning electron microscopy (SEM). (c) 2007 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: chemical preparation; niobates; Perovskites; powders; X-ray methods